2019
DOI: 10.1016/j.cad.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic 3D graphic statics: Reciprocal constructions

Abstract: The recently developed 3D graphic statics (3DGS) lacks a rigorous mathematical definition relating the geometrical and topological properties of the reciprocal polyhedral diagrams as well as a precise method for the geometric construction of these diagrams. This paper provides a fundamental algebraic formulation for 3DGS by developing equilibrium equations around the edges of the primal diagram and satisfying the equations by the closeness of the polygons constructed by the edges of the corresponding faces in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…This paper showed that 3DGS enables us to design infinite efficient light-weight cellular materials for different boundary conditions with various internal topology and force distribution. In this system, the resulted geometry depends on the external force polyhedron, force diagram's internal subdivision, and geometrical degree of freedom of the pin-jointed system [Hablicsek et al 2018]). This method lets us understand the relationship between the internal flow of force, geometry, and external force-flow with their geometrical relationships.…”
Section: Discussionmentioning
confidence: 99%
“…This paper showed that 3DGS enables us to design infinite efficient light-weight cellular materials for different boundary conditions with various internal topology and force distribution. In this system, the resulted geometry depends on the external force polyhedron, force diagram's internal subdivision, and geometrical degree of freedom of the pin-jointed system [Hablicsek et al 2018]). This method lets us understand the relationship between the internal flow of force, geometry, and external force-flow with their geometrical relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Nodal equilibrium is represented as a closed polygon (2D) or polyhedron (3D). Although initially used as a procedural method of analysis and design, recent algebraic formalizations of graphic statics principals have allowed computational graphic statics to resurge as a modern tool in design and analysis [1,19,25,26,37].…”
Section: Geometric Representation Of Forcementioning
confidence: 99%
“…Nodal equilibrium is represented as a closed polygon (2D) or polyhedron (3D). Although initially used as a procedural method of analysis and design, recent algebraic formalizations of graphic statics principals have allowed computational graphic statics to resurge as a modern tool in design and analysis (Van Mele and Block, 2014;Akbarzadeh, 2016;Hablicsek et al, 2019;Nejur and Akbarzadeh, 2021;Mozaffari et al, 2021).…”
Section: Geometric Representation Of Forcementioning
confidence: 99%